Membangun kepercayaan diri dan keterampilan komunikatif anggota PIK-R melalui pelatihan public speaking dan master of ceremony - Nabila Silviana Putri; Anjani Diah Ayu Safitri; Siti Yulaeha; Chyntia Isni Safira Yasmin; Afif Hibatullah; Lintang Ayu Azahra; M. Nur Maulana Rahmadani; Popi Andiyansari; Al Musa Karim (Penamas: Journal of Community Service, 2026)
Public communication skills are a barrier for adolescents due to a lack of self- confidence and mastery of formal communication techniques. This community empowerment activity aims to improve the self-confidence and communicative skills of members of the Youth Information and Counseling Center (PIK-R) Kapanewon Tempel through public speaking and Master of Ceremony (MC) training. The methods used include pre- and post-tests, interactive lectures, demonstrations, direct practice (simulation), and feedback. This activity involved 31 participants from various villages in Kapanewon Tempel. The effectiveness of the activity was evaluated by comparing pre-test and post-test results and observations during the practice session. The results of the activity showed a 15% increase in understanding of basic MC techniques, including language, intonation, material preparation, and body gestures. In addition, participants showed greater courage in appearing and the ability to manage the flow of events more calmly. This training equipped PIK-R members with relevant communication skills for self-development and active roles in community organizations.